Endogeneous regulatory delay and the timing of product innovation - James E. Prieger (University of California, Department of Economics, 2005)
This paper endogenizes the interplay between innovation by a regulated firm and regulatory delay. When product innovation costs fall over time, an extra day of regulatory delay increases time to introduction by more than a day. In the signaling model, the firm therefore times its innovation to communicate its private information about the marginal cost of delay to the regulator. Successful signaling leads the regulator to reduce regulatory delay. The model places testable restrictions on the empirical relationship between innovation delay and regulatory delay. The model is consistent with data gathered from a large U.S. telecommunications provider.
Keywords: L51; L96; 330; Innovation; Zeit; Regulierung; Theorie